Learning styles and performance in building technical course (Research, Society and Development, 2020)
Students of the Federal Network of Professional, Scientific and Technological Education, even though they usually enter after successful selection processes, they also face difficulties to maintain a good performance. Studies in the field, especially those by Felder and Silverman, point out that a significant part of this situation is directly related to learning styles, which are individual behavioral patterns that may imply greater or lesser ease to learn certain subjects. This study presents the results of an investigation that sought to identify the influences of teacher and student learning styles on school performance, taking also into account the didactic methods used. The context analyzed was that of the Integrated Building Technical Course at the IFMG Campus Santa Luzia, specifically in the disciplines of Construction Stability and Mathematics. The methodology consisted fundamentally in the application of a questionnaire adapted to the Brazilian context to characterize the students and teachers’ styles. Among the results, it is emphasized that the best performances were more linked to more flexible styles of students than to a convergence in relation to the teacher's style.